L’innovation de méthodes en urbanisme : freins et leviers d’une entreprise incertaine - Nadia Arab; Elsa Vivant (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article analyses scientific experiments whose goals are to update urban planning methods through the organization of a new form of meeting between urban artists and professionals. In these case studies, the artists are not necessarily called upon to create a specific work, rather to help reflect upon urban space alongside urban development professionals. The artist finds themselves in a frame where concrete choices and decisions must be made about the ways in which a space is designed, where operational actions must be played out and where perceptions must be reshaped. As experimental approaches, they thus merit special attention as well as updated techniques that allow us to immerse ourselves within them and sense experience them in new ways. Further, they create an unfamiliar situation for stakeholders while testing methods and learning from them. The first part of this article describes four cases in which the common denominator is to establish the updating of urban planning methods based on in situ, in vivo approaches to space. It then focuses on the benefits and constraints of these new innovative methods before concluding by concentrating on the promotors of these techniques which we call “entrepreneurs of methods” and who play a key role in the conception and the implementation of these innovations.